Openness and age influence cognitive progression: a longitudinal study - Silvia Stahl Merlin; Sonia Maria Dozzi Brucki (Arquivos de Neuro-Psiquiatria)
Background Some psychological and personality characteristics of individuals seem to determine behavioral patterns that are associated with better health throughout life and, consequently, prevent the progression of early cognitive changes to dementia.